Research on Digital Health Literacy In Germany: A Scoping Review - Ulbrich, Julia; Matusiewicz, David (Gesundheitsökonomie & Qualitätsmanagement, 2024)
Objective Digital health literacy (dHL) is a main future competence in a digital healthcare system. As there are hardly any empirical findings on dHL in Germany, the objective of this scoping review is to assess the current extent of research on dHL in Germany and further research approaches.Methods A Scoping review based on the widely used methodological framework of Arksey and O'Malley was conducted. The databases of PubMed, MEDLINE, CINAHL, APAPsychArticles, SprinerLink and Livivo were searched. A search syntax based on the topic was developed and adapted to the individual databases. The full text of 27 enclosed citations was assessed in detail.Results Research objectives on dHL in Germany mainly focus on studies to measure dHL in (sub-)population(s), on the influence of dHL on certain parameters as well as on the conceptual understanding of dHL in the German context. The definition and measurement of dHL differs and reveals that no common conceptual understanding exists. Recommendations for the promotion of dHL are unconcrete but imply a conceptual further development, target-oriented promotion measures and the integration of further actors of the healthcare system.Conclusions Findings imply further research especially on a common understanding, effective measures, and a holistic approach to successfully promote dHL in Germany.
Keywords: digitalhealth literacy; promotion; concept; germany; scoping review